Matematización en procesos de generación de conciencia ambiental: un estudio en formación de profesores de matemáticas - Macias-Becerra, Erika-Daniela; Ordoñez-Hernández, Laura-Stephanie; Forero-Poveda, Alberto (Revista Científica, 2021)
The main objective of this article is to study the possible relationships between processes and schemes associated with mathematical modeling and the mathematization of environmental phenomena and the elements linked to the generation of environmental awareness, based on an analysis conducted on products elaborated by a group of students, who studied the training space called mathematization of environmental problems and the curriculum project for the Bachelor of Mathematics LEMA program. It also included a group of students of first semester, who, on the contrary, had not formally undergone a mathematical modeling process. The analysis was based on a case study within explanatory qualitative research, which showed an understanding of mathematization, environmental awareness, and the relationship between these two. The analysis carried out on the products and interpretations of students who participated directly in the mathematization of environmental phenomena allows us to state the importance of the use and management of schemes, activities, and methods in mathematical and statistical in processes and to gain an in-depth understanding of the various environmental impacts that manifest themselves in our reality. This is also important for decision-making and the generation of environmental awareness in our communities. This work contributes to fostering spaces for the reflection of our actions as mathematics teachers in processes involving the generation of environmental awareness from mathematics as human activity.